Cell proliferation in Helicobacter pylori associated gastritis and the effect of eradication therapy. Issue 3 (March 1995) - Lynch, D A; Mapstone, N P; Clarke, A M; Sobala, G M; Jackson, P; Morrison, L; Dixon, M F; Quirke, P; Axon, A T
Abstract : Helicobacter pylori causes chronic (type B) gastritis. The 'intestinal' form of gastric cancer arises against a background of chronic gastritis, and prospective epidemiological studies have shown that H pylori is a major risk factor for this. An increase in mucosal cell proliferation increases the likelihood of a neoplastic clone of epithelial cells emerging where there is chronic epithelial cell injury associated with H pylori gastritis. In vitro bromodeoxyuridine labelling of endoscopic antral biopsy specimens was used to measure mucosal cell proliferation in H pylori associated gastritis before and after therapy for H pylori triple infection. Cell proliferation was increased in H pylori associated gastritis patients compared with normal controls and patients with H pylori negative chronic gastritis (p = 0.0001; Tukey's Studentised range). There was no difference in antral epithelial cell proliferation between duodenal ulcer and non-ulcer subjects infected with H pylori (p = 0.62; Student's t test). Antral mucosal cell proliferation fell four weeks after completing triple therapy, irrespective of whether or not H pylori had been eradicated (p = 0.0001). At retesting six to 18 months later (mean = 12 months), however, those in whom H pylori had not been successfully eradicated showed increased mucosal proliferation compared with both H pylori negative subjects at a similar follow up interval and all cases (whether H pylori positive or negative) four weeks after completion of triple therapy (p = 0.024). These findings suggest that H pylori infection causes increased gastric cell proliferation and in this way may play a part in gastric carcinogenesis.